2017 ACM/IEEE International Symposium on Empirical Software Engineering and Measurement (ESEM) 2017
DOI: 10.1109/esem.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Heterogeneity of Contributors in Bug Bounty Programs

Abstract: Background: While bug bounty programs are not new in software development, an increasing number of companies, as well as open source projects, rely on external parties to perform the security assessment of their software for reward. However, there is relatively little empirical knowledge about the characteristics of bug bounty program contributors. Aim: This paper aims to understand those contributors by highlighting the heterogeneity among them. Method: We analyzed the histories of 82 bug bounty programs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The insufficient report quality is a casualty of first-come firstserved response to verified submissions, with hackers sometimes racing to submit a vulnerability. With many hackers concentrating on capitalising from their skills economically, many look to maximise the number of submissions rather than focusing on specific vulnerabilities (Hata et al, 2017). Potentially, this issue is encouraged with admission to private programs.…”
Section: Bug Bounty Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…The insufficient report quality is a casualty of first-come firstserved response to verified submissions, with hackers sometimes racing to submit a vulnerability. With many hackers concentrating on capitalising from their skills economically, many look to maximise the number of submissions rather than focusing on specific vulnerabilities (Hata et al, 2017). Potentially, this issue is encouraged with admission to private programs.…”
Section: Bug Bounty Issuesmentioning
confidence: 99%
“…Without greater incentivisation to outweigh the decreased probability to discover bugs, there is a potential problem with incomplete coverage possibly leading to a false perception of security. The heterogeneity of hacker skillsets may mitigate this problem to some extent (Hata et al, 2017).…”
Section: Bug Bounty Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of companies and FLOSS projects rely on external parties to perform the security assessment of their software for reward called bug bounty program. It is reported that there are non-project-specific bug bounty hunters and they are different from traditional contributors who work on specific projects [10]. Nakasai et al studied the impact of budges donors will get and reported that monetary contributions have impact on software development processes [11].…”
Section: Introductionmentioning
confidence: 99%